EAST ASIAN SUMMER MONSOON VARIABILITY DURING MARINE ISOTOPE STAGE 5 BASED ON SPELEOTHEM δ18O RECORDS FROM WANXIANG CAVE, CENTRAL CHINA - Johnson K.R.; Lynn Ingram B.; Sharp W.D.; Zhang P. (My University, 2006)
Speleothems from Wanxiang Cave, China (33°19′ N, 105°00′ E), located near the northern limit of the East Asian summer monsoon, provide high-resolution records of paleomonsoon variability. We present a simple model for interpreting δ18O shifts in speleothems from this region in which the δ18O of speleothem calcite is inversely related to monsoon intensity. In contrast to observations at higher latitudes, atmospheric temperature has little effect on δ18O of precipitation near Wanxiang Cave. Furthermore, the temperature dependence of calcite-water δ18O fractionation acts in the opposite sense, most likely canceling out the effect of local temperature variations on speleothem δ18O. Given this, the maximum δ18O shift that could occur due only to changes in the composition of the oceanic source region, the amount of rainfall, and the amount of evaporation between full glacial conditions with a weak summer monsoon and full interglacial conditions with a strong summer monsoon is 5.5‰. Accordingly, it is necessary to invoke changes in past atmospheric circulation patterns and in the ratio of summer to winter precipitation to explain the nearly 7‰ range observed in fossil Wanxiang Cave speleothems. Two stalagmites, WXSM 51 and WXSM 52, exhibit more positive δ18O during stadial periods (marine isotope stages [MIS] 8, 6, 5d, 5b, and 2) than during interstadial periods (MIS 9, 5a, 5c, 5e). Thus, East Asian summer monsoon intensity is generally decreased during globally cooler periods and increased during globally warmer periods. We present detailed δ18O records from MIS 5a-5b and 5c-5d. During the MIS 5d-5c transition, summer monsoon intensity increased steadily from 117.6 ka, with a peak in intensity occurring at 106.8 ka, concurrent with Greenland Interstadial 24. During the MIS 5b-5a transition, monsoon intensity increased abruptly at about 85.7 ka, when δ18O decreased by approximately 4‰ in 200 years. Monsoon variability, inferred from the MIS 5c-5d and MIS 5a-5b records, closely coincides with global climate changes observed in the GISP2, Vostok, and SPECMAP records, and with the Northern Hemisphere insolation curve. This suggests that East Asian summer monsoon intensity varies in phase with global climate fluctuations and is largely controlled by variations in Northern Hemisphere incident solar radiation. The MIS 5a-5b and 5c-5d paleomonsoon records from Wanxiang Cave also agree well with other records of Asian monsoon variability indicating that δ18O of speleothems from Wanxiang Cave is a valid proxy for past changes in monsoon intensity. © 2006 Elsevier B.V. All rights reserved.
Keywords: ASIAN MONSOON; MIS 5; OXYGEN ISOTOPES; PALEOCLIMATE; SPELEOTHEM